The Role of the Office of National and Political Affairs in Increasing Political Participation in 2024 Elections: The Evidence of Jambi Province, Indonesia - Inayah, Faras; Subekti, Dimas; Darminto, Citra (Jurnal Pemerintahan dan Kebijakan (JPK), 2026)
This study aims to explain the role of the Office of National and Political Affairs (Kesbangpol) Jambi Province in increasing political participation in the 2024 elections. This research uses a qualitative case study method. Data collection techniques include observation, interviews, and documentation. The results showed that the Jambi Province Kesbangpol Agency was not optimal in increasing political participation in the 2024 elections. The political education program carried out by the Kesbangpol Agency remains formal and ceremonial, without a clear roadmap, and the quality of the education still needs to be questioned. The collaboration carried out by this agency remains formal, with limited integration in the planning and implementation of joint programs with other stakeholders. Furthermore, the Jambi Province Kesbangpol Agency has not utilized digital technology optimally to provide public information about the 2024 elections. Therefore, this research argues that local governments play an essential role in organizing elections. However, these capacities are not optimally exercised due to poorly prepared work plans by representative institutions.